DIPLOMASI PUBLIK TESLA DALAM PENERAPAN ESG PASCASKANDAL TAMBANG KOBALT DI REPUBLIK DEMOKRATIK KONGO - Iswari, Rani Dian (Dinamika Global : Jurnal Ilmu Hubungan Internasional, 2025)
This article analyzes Tesla's public diplomacy strategy in addressing its reputational crisis following the cobalt mining scandal in the Democratic Republic of Congo (DRC). Although not directly involved in mining operations, Tesla faced global criticism for sourcing cobalt from supply chains linked to child labor and human rights abuses. Through a qualitative case study, this research explores how Tesla utilized corporate public diplomacy to rebuild its legitimacy and implement Environmental, Social, and Governance (ESG) principles. Key efforts include transparency through sustainability reporting, stakeholder engagement, and technological innovations like blockchain for supply chain traceability. The study concludes that while Tesla’s public diplomacy strategy improved its image, systemic reforms remain essential for ethical global supply chains.